Hambatan Sosial dalam Pemanfaatan Mekanisme Hukum Formal oleh Masyarakat - Putri Sutami; Dian Austin (Universitas Sains dan Teknologi Komputer, 2025)
This study examines social barriers to the use of formal legal mechanisms in Indonesia using a sequential explanatory mixed-methods design that integrates a large-scale survey with in-depth interviews. The quantitative phase involved 400 respondents who had experienced legal problems within the last five years and was analyzed using logistic regression to identify key social determinants of formal legal use. The results indicate that trust in law enforcement institutions and perceptions of procedural justice significantly increase the likelihood of using formal legal channels, while prior negative experiences and fear of social stigma significantly reduce it. These findings were further elaborated through qualitative interviews, which revealed how institutional distrust, traumatic encounters with legal authorities, community pressure, and concerns over social reputation shape individuals’ legal choices. The study demonstrates that limited engagement with formal legal mechanisms cannot be fully explained by structural constraints alone, but must be understood as a socially constructed phenomenon rooted in everyday experiences and collective perceptions of law. By highlighting the central role of social and psychological factors, this research contributes to socio-legal scholarship on access to justice and suggests that judicial reform should prioritize not only procedural efficiency but also the restoration of public trust and the improvement of state–society relations in legal settings.